The pathophysiological role of novel pulmonary arterial hypertension gene SOX17. Issue 3 (23rd September 2021) - Wu, Yukyee; Wharton, John; Walters, Rachel; Vasilaki, Eleni; Aman, Jurjan; Zhao, Lan; Wilkins, Martin R.; Rhodes, Christopher J.
Pulmonary arterial hypertension (PAH) is a progressive disease predominantly targeting pre-capillary blood vessels. Adverse structural remodelling and increased pulmonary vascular resistance result in cardiac hypertrophy and ultimately failure of the right ventricle. Recent whole-genome and whole-exome sequencing studies have identified SOX17 as a novel risk gene in PAH, with a dominant mode of inheritance and incomplete penetrance. Rare deleterious variants in the gene and more common variants in upstream enhancer sites have both been associated with the disease, and a deficiency of SOX17 expression may predispose to PAH. This review aims to consolidate the evidence linking genetic variants in SOX17 to PAH, and explores the numerous targets and effects of the transcription factor, focusing on the pulmonary vasculature and the pathobiology of PAH. SOX17, a risk gene in PAH, manifests in vivo phenotypes and interacts with key signalling pathways and transcriptional targets in the pathobiology of PAH. Restoration of SOX17 gene expression and signalling may represent a new therapeutic strategy in PAH. https://bit.ly/37ldkIL